Nutrient Content of Tomato as Influenced by Different Sources and Levels of Boron - P.K. Basavaraja; G.K. Mukunda, Altaf Kuntoji*, C.T. Subbarayappa (Journal of the Indian Society of Soil Science, 2021)
A field experiment was conducted to evaluate different sources and levels of boron (B) on nutrient content in tomato in a randomized complete block design with ten treatments and three replications. Boron was applied through borax as soil application and boric acid or boron metalosate as foliar spray. Application of B enhanced the nutrient content in tomato crop (haulm and fruits). The treatment receiving recommended dose of fertilizer (RDF) with 1.1 kg B ha-1 as soil application and 0.05% B (boron metalosate) as foliar spray recorded the highest nutrient contents in both haulm and fruits. The concentration of B in leaf at one day before spray was recorded higher in the treatment T4 receiving RDF + 2.2 kg B ha-1 through borax as soil application, whereas at one week after 1st spray at vegetative stage, one day before 2nd spray and one week after 2nd spray at fruit setting stage significantly higher B content was recorded in T10 treatment consists of RDF + 1.1 kg B ha-1 through borax as soil application followed by 0.05% B through boron metalosate as foliar application compared to RDF (T1). At harvest, concentration of B was significantly reduced in the treatments with respect to other weeks of interval of spray.